Human Umbilical Cord Mesenchymal Stem Cell Differentiation Into Odontoblast-Like Cells and Endothelial Cells: A Potential Cell Source for Dental Pulp Tissue Engineering - Zhang, Shuang; Zhang, Weiwei; Li, Yanping; Ren, Liping; Deng, Haotian; Yin, Xiaowei; Gao, Xu; Pan, Shuang; Niu, Yumei (Frontiers in Physiology, 2020)
Objectives Dental pulp regeneration is considered an ideal approach for treating dental pulp disease. Because pulp is composed of various cells, determining the proper seed cells is critical. We explored the potential of human umbilical cord mesenchymal stem cells (hUCMSCs) as seed cells for dental pulp regeneration. Methods Liquid extract of human treated dentin matrix (LE-TDM) was acquired to culture hUCMSCs. Odontoblast-specific markers were detected by western blot, qRT-PCR, and immunofluorescence assays. Endothelial differentiation of hUCMSCs was examined according to VEGF induction by western blot, qRT-PCR, and Matrigel assays. hUCMSCs and VEGF-induced hUCMSCs (V-hUCMSCs) were also cocultured in vivo for the Matrigel plug assay and in vitro for RNA-sequencing (RNA-seq). Finally, encapsulated mono-cultured hUCMSCs or cocultured hUCMSCs and V-hUCMSCs in scaffolds were injected into the root segments and transplanted into immunodeficient mice for dental pulp regeneration. Results Under LE-TDM induction, hUCMSCs expressed specific odontoblast markers (DSPP, DMP-1, DSP). Under VEGF induction, hUCMSCs expressed functional endothelial markers (CD31, eNOs, vWF). In vivo, the Matrigel plug assay indicated that cocultured hUCMSCs and V-hUCMSCs formed extensive vessel-like structures. RNA-seq results indicated that cocultured V-hUCMSCs exhibited high Hif-1 signaling pathway activity. Both the hUCMSCs mono-culture and coculture groups showed pulp-like tissue regeneration. The cocultured group showed more extracellular matrix and vascularization than the mono-cultured group in vivo. Conclusion hUCMSCs can differentiate into odontoblast-like cells and functional endothelial cells. Cocultured hUCMSCs and V-hUCMSCs formed vessel-like structures and regenerated dental pulp-like tissue. Therefore, hUCMSCs can be used as an alternative seed cell source for angiogenesis and dental pulp regeneration.